QARD WAL IJARAH: A STUDY ON HAJJ FINANCING IN INDONESIA - Risti Lia Sari; Dina Yustisi Yurista; Mohammad Noviani Ardi (Multazam : Jurnal Manajemen Haji dan Umrah, 2021)
Hajj financing product held in Indonesia due to the quota of hajj limited and the cost of going hajj is more expensive than before. But, there are some sharia issues which pertain to the implementation of the qard wal ijarah contract in the reality which is different with what the sharia committee decides. The purpose of this study is to criticize the implementation of the contract in reality and describe its implications both positive and negative. This research uses qualitative research method by using documentation such as hajj report, books, and articles. The results of this study describes that Hajj financing on the one hand give the positive impact (maslahah), while on the other hand has the negative impact (mafsadah). This research contributes to the government and the sharia committees in order to regulate back Hajj management system and also its contract since there are several issues regard the implementation of the contract of hajj financing which is indicated non sharia compliant.